2015
DOI: 10.1016/j.icarus.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evolution of Saturn’s polar temperatures and composition

Abstract: The seasonal evolution of Saturn's polar atmospheric temperatures and hydrocarbon composition is derived from a decade of Cassini Composite Infrared Spectrometer (CIRS) 7-16 µm thermal infrared spectroscopy. We construct a near-continuous record of atmospheric variability poleward of 60• from northern winter/southern summer (2004, L s = 293The hot tropospheric polar cyclones that are entrained by prograde jets within 2-3• of each pole, and the hexagonal shape of the north polar belt, are both persistent featur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 48 publications
10
92
0
Order By: Relevance
“…Our modelled temperature profiles suggest that auroral-induced aerosols confined in the polar hood could significantly contribute to this polar warming, although we cannot rule out that other processes, such as adiabatic heating due to subsidence, also play a part in the warming. This hypothesis has been suggested in previous studies (Orton & Yanamandra-Fisher 2005;Sánchez-Lavega et al 2006;Fletcher et al 2008Fletcher et al , 2015, but this is the first time that this effect is estimated.…”
Section: Modelling the Haze's Radiative Impactsupporting
confidence: 50%
See 1 more Smart Citation
“…Our modelled temperature profiles suggest that auroral-induced aerosols confined in the polar hood could significantly contribute to this polar warming, although we cannot rule out that other processes, such as adiabatic heating due to subsidence, also play a part in the warming. This hypothesis has been suggested in previous studies (Orton & Yanamandra-Fisher 2005;Sánchez-Lavega et al 2006;Fletcher et al 2008Fletcher et al , 2015, but this is the first time that this effect is estimated.…”
Section: Modelling the Haze's Radiative Impactsupporting
confidence: 50%
“…• S (Fletcher et al 2008(Fletcher et al , 2015. Future measurements of the temperature and haze opacities in the polar regions, in particular the monitoring of the formation -or not -of a northern counterpart of the south polar hood, will be extremely valuable for the study of the chemistry and radiative budget in Saturn's polar stratosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The hexagonal shape of the structure suggests that it originates at tropospheric altitudes: in fact, the temperatures retrieved in Saturn polar regions from data by the Composite Infrared Spectrometer on board Cassini (Fletcher et al 2008(Fletcher et al , 2015 showed a circular stratospheric thermal field, not giving any hint of a possible hexagonal shape. Even stellar occultation data from VIMS at high latitude do not observe any 3700 nm doublet signature in the stratosphere (Kim et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we use four different sets of wind profiles at cloud level: (i) June 2013 (early northern summer) from latitudes 68° to 90° (all latitudes in this study are planetographic, Antuñano et al, ), (ii) December 2008 (late northern winter) from latitudes 70° to 84° (García‐Melendo et al, ), (iii) October/December 2008 from latitudes −68° to −90° (Antuñano et al, ), and (iv) October 2006 (southern summer) from latitudes −68° to −90° (Sánchez‐Lavega et al, ), and four data sets of zonally averaged temperature profiles for pressures between 1 and 1 bar. Due to the lack of simultaneous measurements of winds and temperatures during the Cassini mission, the temperature fields for the months of interest (i.e., June 2013, December 2008, and October 2006) were obtained by interpolating the existing temperature measurements over the whole Cassini mission, and extracting only the months where wind measurements were available (see Fletcher et al, , ). Temperatures were retrieved from CIRS focal plane 1 (10–600 cm −1 ), sensing the 80–800‐mbar range, and focal plane 4 (1,100–1,400 cm −1 ), sensing the 0.5–5.0‐mbar range.…”
Section: Database and Methodologymentioning
confidence: 99%
“…In order to estimate the error introduced in the QGPV due to errors on the zonal wind profiles (with a mean standard deviation of 7 m s −1 ; Antuñano et al, ), and the temperature profiles (around 2 K at the stratosphere above trueτ~=140 and 0.5 K at the troposphere; Fletcher et al, ), we have added random perturbations of a magnitude equal to the error to the zonal wind and temperature profiles, respectively, and analyzed the variations in QGPV caused by these perturbations. Results are discussed in section .…”
Section: Database and Methodologymentioning
confidence: 99%